2009
DOI: 10.1103/physreva.79.042718
|View full text |Cite
|
Sign up to set email alerts
|

Observation of interspecies Feshbach resonances in an ultracold Rb-Cs mixture

Abstract: We report on the observation of interspecies Feshbach resonances in an ultracold, optically trapped mixture of Rb and Cs atoms. In a magnetic field range up to 300 G we find 23 interspecies Feshbach resonances in the lowest spin channel and 2 resonances in a higher channel of the mixture. The extraordinarily rich Feshbach spectrum suggests the importance of different partial waves in both the open and closed channels of the scattering problem along with higher-order coupling mechanisms. Our results provide, on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
165
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(170 citation statements)
references
References 71 publications
5
165
0
Order By: Relevance
“…The high efficiency of the sympathetic cooling implies a large interspecies elastic collision rate. This is consistent with the latest theoretical refinement of the interspecies collision potential [33], which shows excellent agreement with the published Feshbach spectrum [26,34] and indicates a background interspecies scattering length of ≈650a 0 (a 0 = 0.0529 nm) for the states used in this work. We continue this cooling until Majorana losses begin to limit the lifetime of the sample.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…The high efficiency of the sympathetic cooling implies a large interspecies elastic collision rate. This is consistent with the latest theoretical refinement of the interspecies collision potential [33], which shows excellent agreement with the published Feshbach spectrum [26,34] and indicates a background interspecies scattering length of ≈650a 0 (a 0 = 0.0529 nm) for the states used in this work. We continue this cooling until Majorana losses begin to limit the lifetime of the sample.…”
supporting
confidence: 79%
“…Both species have been separately condensed and the intraspecies two-body interactions are now well understood [24,25]. Numerous interspecies Feshbach resonances have been observed [26], permitting, in principle, the control of the interspecies interactions and the creation of RbCs Feshbach molecules. Crucially, the RbCs molecule in the rovibrational ground state is stable against atom exchange reactions of the form RbCs + RbCs → Rb 2 + Cs 2 , unlike the KRb molecule [27].…”
mentioning
confidence: 99%
“…Population imbalanced dilute mixtures of degenerate ultracold atoms, either Bose-Fermi [83][84][85][86][87][88] or Bose-Bose [89][90][91][92][93][94] mixtures, in which the role of the majority many-body environment is played by bosons, are the ideal settings in which to explore this rich physics. We require sufficiently low temperatures for which the bosonic environment will condense and can be modeled as a weakly interacting BEC.…”
Section: Discussionmentioning
confidence: 99%
“…Bose-Bose mixtures of Rb 87 -K 41 [90,92] and Rb 87 -Cs 133 [91,94], as well as the Bose-Fermi mixture of Na 23 -K 40 [88], are promising candidates in which to realize the polaronic physics of heavy impurities in BECs. In the three systems considered, the heavy impurities, respectively Rb 87 , Cs 133 , K 40 , have intrinsic mass ratio M/m ≈ 2 with respect to the BEC atoms, which can be further enhanced by a state-selective optical lattice.…”
Section: A Relation To Experimental Systemsmentioning
confidence: 99%
“…Due to proximity of K(4p) and Rb(5p) energies, the energy of low-lying electronic states of KCs is similar to the ones in the RbCs molecule, however, KCs possess larger permanent electric dipole moment. The RbCs molecule has been already studied in ultracold conditions [7,8,9]. In particular, the recent quantum dynamics simulation of the mixed A 1 Σ + and b 3 Π Ω states of RbCs in a time-dependent wave-packet approach [6] demonstrated that the pump -dump picosecond pulsed laser scheme could be efficient to form ultracold heteronuclear diatomic molecules in highly bonded ground X 1 Σ + state.…”
Section: Introductionmentioning
confidence: 99%